Inventarisasi Permudaan Meranti (Shorea spp.) Pada Arboretum Kawasan Universitas Riau Kota Pekanbaru Provinsi Riau - Wahyu, Elvan; Sribudiani, Evi; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Meranti (Shorea spp.) is an important commodity which is one of the major timber producing commercial plants in Indonesia. In worldwide trading, meranti group is divided into four major groups, namely: group of red meranti, yellow meranti group, white meranti group and group of turvy meranti. Purpose of the implementation of this study was to determine the availability, amount, and regeneration dominance of meranti (Shorea spp.) as well as a tree diagram in the profile Riau University Arboretum area. Techniques of data collection is done by using the method purposive sampling or transect lines. Entire observation contains regeneration sample plots, namely regeneration meranti much as 9 rods (2.76%) while  the  317  rods  (97.24%)  are  type  of  non  meranti.  Meranti  Shorea parvistipulata Heim  and  Shorea  parvifolia were found.  INP  at  a rate  of 0% seedling, sapling rate of 2.28%, 15.20% for poles and tree level of 57.03%.   Keyword : inventore, regeneration, meranti, arboretum